Female Gender Difficulties in Higher Education: Case Study of Tunisian Universities - Chekir, Nihel; Salem, Yassine Ben (Journal of Engineering Education Transformations, 2025)
This paper presents some results of a survey carried out as an activity of the project “SOLIDAIRES” implemented by the Tunisian Association for Science and Research and funded by the United Nations Development Programme in the framework of ODD16 portfolio. It aims to identify the difficulties encountered by female gender students at the University of Gabes. Four higher education institutions are covered by this study: the National Engineering School of Gabes (ENIG), the Higher Institute of Applied Sciences and Technology (ISSAT), the Higher Institute of Technological Studies (ISET) and the Faculty of Science (FSG). The results of the survey show that besides the problems, already known, and encountered by most students, females because of their gender suffer from other specific difficulties which are unknown or less considered. The main difficulty that faces females in university is harassment. Much more effort should be put into leaving no one behind in the university.